2015
DOI: 10.14744/nci.2015.87487
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of aberrations and visual quality differences between myopic and astigmatic eyes before and after contact lens application

Abstract: OBJECTIVE:To evaluate the aberration and visual quality differences between myopic and astigmatic eyes before and after contact lens application by using corneal aberrometer and low- contrast sensitivity chart.METHODS:Eighty eyes of 40 patients were included in this study. Patients were divided into two groups as myopic (40 eyes, n=20) and astigmatic groups (40 eyes, n=20). We used aspheric Balafilcon A (Purevision and Purevision Toric Bausch&Lomb, Rochester, USA) lenses for each group. Corneal aberrations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In a study evaluating the effect of CL insertion on visual quality and aberrations, it was found that transparent CL did not change low contrast sensitivity. 13 We think that the multiple light reflections formed by the pre-lens tear film and the anterior and posterior surface of the CL are effective in reducing the contrast sensitivity at high frequencies in our study. In the literature, it has been stated that the reason for the decrease in contrast sensitivity with CL insertion is induced aberrations.…”
Section: Discussionmentioning
confidence: 62%
“…In a study evaluating the effect of CL insertion on visual quality and aberrations, it was found that transparent CL did not change low contrast sensitivity. 13 We think that the multiple light reflections formed by the pre-lens tear film and the anterior and posterior surface of the CL are effective in reducing the contrast sensitivity at high frequencies in our study. In the literature, it has been stated that the reason for the decrease in contrast sensitivity with CL insertion is induced aberrations.…”
Section: Discussionmentioning
confidence: 62%
“…This result is in line with previous studies that have found improved visual quality and acuity with toric SCLs in low and moderate astigmatic eyes. 14 , 15 We believe that with a good SCL-cornea adaptation process, the mechanical properties of contact lenses and the toric designs result in fewer aberrations with toric lenses compared to glasses.…”
Section: Discussionmentioning
confidence: 99%